The case for thermalization as a contributor to the [C ii] deficit. Issue 1 (20th February 2021) - Sutter, Jessica; Dale, Daniel A; Sandstrom, Karin; Smith, J D T; Bolatto, Alberto; Boquien, Mederic; Calzetti, Daniela; Croxall, Kevin V; De Looze, Ilse; Galametz, Maud; Groves, Brent A; Helou, George; et al.
ABSTRACT: The [C ii ] deficit, which describes the observed decrease in the ratio of [C ii ] 158 μ m emission to continuum infrared emission in galaxies with high star formation surface densities, places a significant challenge to the interpretation of [C ii ] detections from across the observable universe. In an attempt to further decode the cause of the [C ii ] deficit, the [C ii ] and dust continuum emission from 18 Local Volume galaxies has been split based on conditions within the interstellar medium where it originated. This is completed using the Key Insights in Nearby Galaxies: a Far-Infrared Survey with Herschel (KINGFISH) and Beyond the Peak (BtP) surveys and the wide-range of wavelength information, from UV to far-infrared emission lines, available for a selection of star-forming regions within these samples. By comparing these subdivided [C ii ] emissions to isolated infrared emission and other properties, we find that the thermalization (collisional de-excitation) of the [C ii ] line in H ii regions plays a significant role in the deficit observed in our sample.